Monica - Clowes, Daniel (Fantagraphics Books, Inc., 2023)
Monica is a series of interconnected narratives that collectively tell the life story--actually, stories--of its title character. Clowes calls upon a lifetime of inspiration to create the most complex and personal graphic novel of his distinguished career. Rich with visual detail, an impeccable ear for language and dialogue, and thrilling twists, Monica is a multilayered masterpiece in comics form that alludes to many of the genres that have defined the medium--war, romance, horror, crime, the supernatural, etc.--but in a mysterious, uncategorizable, and quintessentially Clowesian way that rewards multiple readings. -- Adapted from Amazon.com.